BOOK REVIEW: WULFSTAN, "OLD ENGLISH LEGAL WRITINGS", ED. AND TRANS. ANDREW RABIN. (DUMBARTON OAKS MEDIEVAL LIBRARY 66.) CAMBRIDGE, MA: HARVARD UNIVERSITY PRESS, 2020. PP. XXXIX, 439. - CRIȘAN, Andrei (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Perhaps the best documented fact about Archbishop Wulfstan of York is that he is not sufficiently documented at all. Second perhaps only to Ælfric of Eynsham in his theological endeavours, Wulfstan (d. 1023) was also the foremost statesman of his age, as advisor to kings Æthelred (978 – 1013) and Cnut (1016–1035). Moreover, during his lifetime, he served in three of England’s most influential ecclesiastical offices: the bishoprics of London and Worcester, and the archbishopric of York, holding the latter two in plurality until 1016. Little is known about his life before he was created bishop of London, though we may safely assume that he had deep ties with the Benedictine reform and was a monk or even an abbot before his ascension to the episcopate.